Application of cost accounting systems in an enterprise = Zastosowanie systemów rachunku kosztów w przedsiębiorstwie - Kużdorowicz, Paweł; Kużdorowicz, Dorota (Zielona Góra: Faculty of Economics and Management Press)
The article discusses the issue of allocation of costs in the normal and actual cost accounting systems. A procedure of dump (conversion) of the normal into actual costs using data flows has been presented. The article presents an example of applying the designed procedure illustrating the links between cost centre, cost objects and income objects accounting.
Keywords: systemy rachunku kosztów; koszty normalne; koszty bieżące; alokacja kosztów; normal costs; actual costs; data flows; allocation of costs